Raising Drug Awareness Through Interactive Socialization: A Case Study at SMK Taruna Jaya Gresik, Indonesia - Wardana, Dodi Jaya; Nurjanah, Eka; Sari, Anggun Purnama (Universitas Muhammadiyah Magelang, 2025)
Drug abuse among adolescents is a serious issue that requires approaches aligned with contemporary developments. An interactive approach is one of the most effective methods of socialization for reaching and actively engaging students. This community service initiative aimed to raise students’ awareness and understanding of the dangers of drug abuse through digital education based on interactive methods. In addition, it provided deeper insights into the harmful effects of drugs and strategies for prevention. The program was conducted at SMK Taruna Jaya Gresik by integrating various digital learning media, such as educational video screenings, direct material presentations on the dangers of drug abuse, and the use of social media platforms for anti-drug campaigns through poster dissemination. The outcomes of the program indicated a significant improvement in students' understanding of drug-related issues, as well as increased enthusiasm and participation in the socialization activities. Digital education proved to be an effective and engaging method for delivering drug prevention messages in school settings, particularly among digital-native students such as those at vocational high schools. Overall, this awareness campaign successfully enhanced the knowledge of SMK Taruna Jaya Gresik students regarding the dangers of drug abuse and contributed to the development of more responsible mindsets and attitudes among them.